Remixing the classroom : toward an open philosophy of music education - Allsup, Randall Everett (Counterpoints (Bloomington, Ind.), 2016)
"In a delightfully self-conscious philosophical "mash-up", Randall Everett Allsup provides alternatives for the traditional master-apprentice teaching model that has characterized music education. By providing examples across the arts and humanities, Allsup promotes a vision of education that is open, changing, and adventurous at heart."--back cover
Keywords: Music : Instruction and study; opetus; laatu; oppiminen; avoimuus; musiikkikasvatus